Factors Influencing Activity-Based Costing Success: A Review - Zhang, Y.F.; Isa, C.R. (2010)
In today’s advanced manufacturing environment and competitive environment, accurate costing information is crucial for all businesses, such as manufacturing firms, merchandizing firms, and service firms. Argued as superior to traditional volume-based costing system, Activity-Based Costing system (ABC) has increasingly attracted the attention of practitioners and researchers alike as one of the strategic tools to aid managers for better decision making. The benefits of ABC system and its impacts on companies’ performance have motivated numerous empirical studies on ABC system and it is considered as one of the most-researched management accounting areas in developed countries. Previous research on ABC have examined pertinent issues related to ABC implementation such as the levels of ABC adoption in various countries, the reasons for implementing ABC, the problems related to ABC and the critical success factors influencing ABC. This paper reviews the research on ABC carried out within the last decade, from 1995-2008, and from the review research gaps are identified. Specifically, this paper examines the selection of factors influencing ABC successful implementation, variables used by previous research. The review revealed that past research concentrated mainly on behavioral, organizational, and technical variables as the main determinants of ABC success. Based on the research gaps identified, suggestions for future research are also provided. Keywords: Activity-Based Costing, ABC Success, Advanced Manufacturing Environment